A kortárs magyar líra oroszversei kelet-közép-európai kontextusban - Rálik Alexandra (2025)
The focus of the dissertation is on the particular corpus of Hungarian poetry that have been called "Russian poems" since István Baka's poems under the pseudonym Stepan Pehotny: besides Baka, the works of László Király, Ferenc András Kovács and László Bogdán, which were published as independent volumes under the names of their Russian alter egos. The necessity of the research was justified by the fact that, although the reception of the individual poets has already dealt to a varying degree with these poetry cycles, which can be read along the lines of both Hungarian and Russian codes, the dialogue between the four authors and their texts has not yet been discussed in any depth, beyond a mention or superficial comparison. The study does not limit itself to a philological and comparative juxtaposition of the four Russian-Hungarian poetry volumes, namely, Baka's Sztyepan Pehotnij testamentuma (1994), László Király's Beűzetés (1995), a collection dedicated to the poems of fictional Al. Nyezvanov, András Ferenc Kovács's Alekszej Pavlovics Asztrov hagyatéka (2010) and László Bogdán's works published under the pseudonym Vassily Bogdanov (especially A végzet kirakós játékai (2013) and Az illuzionista és a szörnyeteg (2015)). Following the philological-theoretical framing, the thesis explores how these so-called "Russian poems" are understood today in the dialogue of the four poets through the use of three close-textual interpretive focuses: the relationship between the paratextual web and poetic mystification, the poetic significance of the exiled poet archetype in the cycles, and possible ironic interpretations of the works under study. In addition to a closer reading of the texts, the thesis also attempts to explore parallels in the literature of the East-Central European region (primarily Polish and Slovak, partly Serbian), thus asking to what extent the poetic dialogicity of "Russian poems" is peculiarly Hungarian, and how the Russian codes of neighbouring literatures might finetune the domestic reception.